PARADIGMA PENDIDIKAN ALTERNATIF: MAJELIS TAKLIM SEBAGAI WADAH PENDIDIKAN MASYARAKAT - Amatul Jadidah; Mufarrohah (LP3M IAI Al-Qolam Malang, 2016)
Majelis taklim is one place that effectively became the venue for education and propagation of Islam since the time of the Prophet until now. it socializes the teachings of Islam in building an advanced, independent and civilized society (khair ummah), provides solutions for both men and women. It functions as center for value of peace, center for community development, and the agent of social control. Majelis taklim imitates the way The Prophet Muhammad delivered revelations that he received to his companions. He did the taâ€™lim in some places such as DÄr al-ArqÄm, house of the Prophet, his companionsâ€™ houses, and al-shuffah. He also provides certain days to teach religion for women. Keywords: Majelis taklim, history, functions, empowerment